An injectable PEG-like conjugate forms a subcutaneous depot and enables sustained delivery of a peptide drug. (March 2023) - Ozer, Imran; Slezak, Anna; Sirohi, Parul; Li, Xinghai; Zakharov, Nikita; Yao, Yunxin; Everitt, Jeffrey I.; Spasojevic, Ivan; Craig, Stephen L.; Collier, Joel H.; Campbell, Jonathan E.; D'Alessio, David A.; et al.
Abstract: Many biologics have a short plasma half-life, and their conjugation to polyethylene glycol (PEG) is commonly used to solve this problem. However, the improvement in the plasma half-life of PEGylated drugs' is at an asymptote because the development of branched PEG has only had a modest impact on pharmacokinetics and pharmacodynamics. Here, we developed an injectable PEG-like conjugate that forms a subcutaneous depot for the sustained delivery of biologics. The PEG-like conjugate consists of poly[oligo(ethylene glycol) methyl ether methacrylate] (POEGMA) conjugated to exendin, a peptide drug used in the clinic to treat type 2 diabetes. The depot-forming exendin-POEGMA conjugate showed greater efficacy than a PEG conjugate of exendin as well as Bydureon, a clinically approved sustained-release formulation of exendin. The injectable depot-forming exendin-POEGMA conjugate did not elicit an immune response against the polymer, so that it remained effective and safe for long-term management of type 2 diabetes upon chronic administration. In contrast, the PEG conjugate induced an anti-PEG immune response, leading to early clearance and loss of efficacy upon repeat dosing. The exendin-POEGMA depot also showed superior long-term efficacy compared to Bydureon. Collectively, these results suggest that an injectable POEGMA conjugate of biologic drugs that forms a drug depot under the skin, providing favorable pharmacokinetic properties and sustained efficacy while remaining non-immunogenic, offers significant advantages over other commonly used drug delivery technologies. Graphical abstract: Synopsis: The objective of this study was to develop a next-generation polymer conjugate technology that improves upon PEG's pharmacokinetic benefits while overcoming its immunogenicity and antigenicity limitations. We improve upon the PK benefits of PEG by designing an injectable POEGMA conjugate that achieves sustained release of a peptide drug from a s.c. injection site into the blood and that, when in blood, extends half-life of the conjugated drug. We achieved this by synthesizing POEGMA copolymers with varying oligoethylene glycol side chain lengths (A) allowing to phase transition between soluble and insoluble state, indicated by changes in optical density (B). The resulting optimal POEGMA conjugate of a peptide drug showed longer pharmacokinetics (C) and higher efficacy than molecular weight (Mw ) and hydrodynamic size (Rh ) matched PEG conjugates. The scientific and translational significance of this work is three-fold. First, this manuscript showcases the first use of PEG-like polymers in sustained-drug delivery while addressing its immunogenicity limitations. Second, the injectable POEGMA conjugate overperforms the sustained delivery formulation of the peptide drug used in the clinic, indicating the power of the platform. Lastly, the application of the injectable POEGMA conjugate technology expands beyond the conjugated peptide drug and applies to broader class of biologics. Image 1